Synthesis of Zeolite-A From Oil Palm Shell Ash for Ferrous Metal Adsorption in Borehole Water - Koloay, Fricha Febriani Paula; Sunarti, Sunarti; Manuhutu, Julita Beatrik (Indonesian Journal of Chemical Research, 2024)
Research has been conducted to adsorb Fe (III) ions in borehole water from Haruru Village, Central Maluku District, and artificial wastewater using A-type zeolite synthesized from oil palm shell ash. The oil palm shell ash was chemically activated by washing with 2 M HCl, serving as a source of SiO2. The synthesized zeolite A underwent characterization using X-ray diffraction (XRD) to determine its crystallinity. Batch adsorption of Fe (III) ions using zeolite A in borehole water and artificial wastewater was performed, involving variations in contact time and adsorbed iron concentration, and was analyzed using atomic absorption spectroscopy. The XRD analysis results indicated that the peaks of zeolite A were more pronounced at a NaOH mass of 93.75 grams, totaling ten peaks. The analysis of the initial concentration of Fe (III) ions in borehole water was 1.2151 ppm, while in artificial wastewater, it was 2.00 ppm. The optimum capacity and efficiency of zeolite A for Fe (III) ions in borehole water from Haruru Village were observed at a contact time of 40 minutes, with a capacity value of 0.1558 mg/g and an efficiency of 10.26%.